2001
DOI: 10.1097/00005768-200106000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Methods for estimating the maximal lactate steady state in trained cyclists

Abstract: Both the (simulated) 5-km and 40-km TT can be used to estimate the MLSS in cyclists. In addition, HLa at MLSS shows a large degree of variation between riders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 14 publications
7
48
0
5
Order By: Relevance
“…Such testing procedures require the presence of an athlete in the laboratory for several days, which can have a detrimental effect on the training program. To eliminate this problem, some researches try to determine the MLSS indirectly, based on a single incremental test (Heck et al, 1985;Jones et al, 1988;Poole, 1988;Beneke, 1996;McLellan, 1992;Laplaud et al, 2005;Figueira et al, 2008) and on filed tests (Hoogeveen et al, 1997;Harnish et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Such testing procedures require the presence of an athlete in the laboratory for several days, which can have a detrimental effect on the training program. To eliminate this problem, some researches try to determine the MLSS indirectly, based on a single incremental test (Heck et al, 1985;Jones et al, 1988;Poole, 1988;Beneke, 1996;McLellan, 1992;Laplaud et al, 2005;Figueira et al, 2008) and on filed tests (Hoogeveen et al, 1997;Harnish et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…However, similarly to the findings of others, there was a significant increase in workload Although a number of research groups have attempted to reduce the number of tests used to establish MLSS [103,125,129,[139][140][141] , further questions relating to the MLSS Harnish, Swensen and Pate [127] Female (n = 3) and male (n = 6) cyclists …”
Section: Changes In Mlss With Trainingmentioning
confidence: 66%
“…For example, running velocity at MLSS has been shown to correlate strongly with 8 km running performance (r = 0.92; p < 0.05) in well-trained men (n = 13) [125] , and with sprint triathlon performance time (750 m swim, 20 km cycle, 5 km run; r = 0.83; p < 0.05) in moderately-trained male triathletes (n = 10) [126] . Furthermore, cycling velocity at MLSS correlated with 40 km cycling time trial velocity (r = 0.84; p < 0.05) in competitive cyclists (n = 3 women and 6 men) [127] . Additionally, an agreement between MLSS intensity and the intensity sustained during performance trials has been reported whereby there was no significant difference between mean 8 km running velocity (16.01 ± 0.32 km·h ; p > 0.05) [125] , nor between the velocity (36. , respectively; all p > 0.05) [127] .…”
Section: Relationship Between Mlss and Endurance Performancementioning
confidence: 89%
See 2 more Smart Citations